O idoso e a arte na UNATI - Godoy, Kathya Maria Ayres de [UNESP] (2015)
In order to develop a university extension program for the public Senior Citizens, The Art Institute of Unesp, through its Local Core Unesp Unati in partnership with the Center of the Rectory , offers typical courses and events in the areas of Visual Arts , Theatre, Dance and Music . The proposed activities seek proximity and interaction of these people to the art world, enabling discussion of issues.